Technostress and Telecommuting in the Context of Covid-19: Evidence from Cambodia’s Higher Education Institutes - Ly, Romny; Ly, Bora (SEISENSE (PRIVATE) LIMITED, 2022)
Closures of educational establishments owing to the COVID-19 pandemic have impacted individuals globally. Educational organizations of all levels have been compelled to use online instruction because comprehensive safety precautions have been taken to minimize the spread of disease during the COVID-19 contagion, which has increased technostress. Both public and private organizations utilized these strategies, allowing the individual to work virtually. Purpose- This work examines the association between the perceived technostress attributes and instructors in Cambodian academic institutions during the COVID-19 pandemic. Design/Methodology- It used a quantitative method and constructed a research instrument to examine (340 participants) of public and private instructors service during the outbreak. Additionally, the data was collected and analyzed using structural equation modeling (SEM). Findings- The study revealed that technostress had a substantial effect on the gender, age, and working experience of educators. Hence, given the rapid evolution of ICT trends, it is appropriate to design practical training and wellness programs to alleviate technostress and foster a sense of technological competence and personal relevance.